ANALISIS ETIKA PROFESI AKUNTANSI PERSPEKTIF AL-QURAN - SEPTIAN ARIEF BUDIMAN (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2018)
Capital Islamic Organization has developed its own accounting code of ethics for professional members and accountants. This study attempts to explain the accounitng code of ethics and is more useful for values and norms for both members and organizations and makes the Quran the basis of its thinking. The methodology of this research is qualitative by observing and studying from books, various articles, research results, and based on the Qur'anic commentary, Al-Hadith as well as other related books.This shows us that Islamic accounting ethics codes ensure the best results for organizations and members.